Rethinking State-Law Relations Through the Kelsen-Schmitt Debate: A Critical Introduction - Erdal Kurğan (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This article examines the law-state relationship in the modern state by comparing the ideas of Carl Schmitt and Hans Kelsen. In this context, firstly, what modern law is and where its differences emerge from will be discussed. Then, the article examines Hans Kelsen's conceptualization of 'Grundnorm', which created the constitution(s) in the modern state(s), as a source of legitimacy in the modern state. The law-state relationship that Kelsen builds on the basis of his 'Pure Theory of Law' is compared to the situation in which Carl Schmitt considers law as the 'decision' of the sovereign. Although Kelsen has accepted law as thing-in-itself and intensified his efforts to build an objective science, the juridical science presents a legitimacy in factual order; even if it was not Kelsen’s goal. Kelsen, however, neglects what is political and failed to examine the appearance of factual order or law in practical social order and their relationship. On the other hand, Schmitt did not much get closer to Kelsen’s approach- building the law with Grundnorm- with his emphasis on sovereignty as the constituent will and unique source of legitimacy. Over what is political and political unity, Schmitt’s approach is based on factual order by defining the law over extraordinary “decision” of the sovereign which is identical with the society/people. The approach to understand the modern state in this article both attaches importance to the Kelsen’s emphasis on the juridical science and attaches equivalent value to the notion of sovereignty which Schmitt rightfully developed. In the last part, this article argues that the law-state relationship in the modern state emerged with both Grundnorm and 'sovereignty', that is, in the partnership of both.